Persepsi Pengunjung terhadap Daya Tarik Wisata di Agrowisata Subak Sembung Pada Era New Normal - DAMAYANTI, KADEK DWI; ANGGRENI, I G. A. A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p15, 2022)
Visitor’s Perception of Tourism Attraction in Subak Sembung Ecotourism  in The New Normal Era Denpasar city has environmentally based tourist attraction (ecotourism) subak agriculture in the middle of the city that is visited by many people. However, tourist behavior changes in the normal new era. So this study aims to determine the perception of visitors to the tourist attraction in Agrotourism Subak Sembung in the new normal era. The research was conducted at Agrotourism Subak Sembung in March 2021. A close questionnaire is used in data collection, which is distributed directly and filled out online through Google Form. A sample of 100 respondents are taken with nonprobability sampling techniques. The data is collected then analyzed using descriptive analysis techniques with likert scale and SPSS 21 software. The results indicate that the average percentage of the entirety description of the respondents' answers covering the three aspects in these variables are 71.3% in the agreement category that the Covid 19 virus prevention facilities and infrastructure in the Subak Sembung Agrotourism area have not met the standards. Visitors also agree that if the addition of these facilities and infrastructure will make visitors feel safer and more comfortable in visiting, even though some visitors have obeyed health protocols for themselves .